Jane Austen’s Women in Her Novels - Akhmedova Hilola Shavkatovna (Proceedings of The ICECRS, 2019)
Austen’s Women – that is, women minus the men – is in this sense anachronistic because it presents the audience with a colourful parade of misguided, downtrodden, ignorant and misshapen female characters who begin to visibly unravel once they have been torn loose from the social system that oppressed them.